2005
DOI: 10.1074/jbc.m409925200
|View full text |Cite
|
Sign up to set email alerts
|

Extended Neck Regions Stabilize Tetramers of the Receptors DC-SIGN and DC-SIGNR

Abstract: The human cell surface receptors DC-SIGN (dendritic cell-specific intercellular adhesion molecule-grabbing nonintegrin) and DC-SIGNR (DC-SIGN-related) bind to oligosaccharide ligands found on human tissues as well as on pathogens including viruses, bacteria, and parasites. The extracellular portion of each receptor contains a membrane-distal carbohydrate-recognition domain (CRD) and forms tetramers stabilized by an extended neck region consisting of 23 amino acid repeats. Cross-linking analysis of full-length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
219
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(241 citation statements)
references
References 30 publications
21
219
1
Order By: Relevance
“…The presence of Man␣1-2Man enhances the affinity of oligomannose toward these receptors, even though by itself this disaccharide binds only slightly more strongly than mannose. The CRD has an intrinsically high affinity for oligomannose structures, and tetramerization likely provides further avidity enhancements for arrays of such structures (6,26). The ability of DC-SIGN and DC-SIGNR to bind high mannose glycans in multiple orientations may facilitate this multivalent binding of clusters of CRDs to glycans displayed in various arrangements on the surface of the virus, as proposed previously for cell surface recognition by mannose-binding proteins (22).…”
mentioning
confidence: 88%
“…The presence of Man␣1-2Man enhances the affinity of oligomannose toward these receptors, even though by itself this disaccharide binds only slightly more strongly than mannose. The CRD has an intrinsically high affinity for oligomannose structures, and tetramerization likely provides further avidity enhancements for arrays of such structures (6,26). The ability of DC-SIGN and DC-SIGNR to bind high mannose glycans in multiple orientations may facilitate this multivalent binding of clusters of CRDs to glycans displayed in various arrangements on the surface of the virus, as proposed previously for cell surface recognition by mannose-binding proteins (22).…”
mentioning
confidence: 88%
“…The type and number of the neck-region repeats are important in dimer formation and stabilization of protein tetramers. 5 Thus, neck-length variation could influence the pathogen-binding properties of these lectins. In previous analyses in primates, 1 CD209 and CD209L have variable numbers of repeats.…”
Section: Introductionmentioning
confidence: 99%
“…studies demonstrated that repeat domains of DC-SIGN and L-SIGN contribute to the overall integrity of the tetramer on the cell surface (16,17). To investigate the impact of the repeat region of L-SIGN on HIV-1 trans-mission, we obtained Raji cells expressing L-SIGN with five, six, or seven repeats and tested these cells in HIV-1 infection assays.…”
Section: Different Allelic Forms Of L-sign Do Not Support Hiv-1 Transmentioning
confidence: 99%
“…Although no structure of dimeric or tetrameric DC-SIGN is currently available, inferences regarding the positioning of Trp-258 relative to other DC-SIGN subunits can be made using a model of the tetrameric L-SIGN receptor (Fig. 9B), which was constructed from the crystal structure of the L-SIGN dimer (16,45). In this model, Lys-270, the L-SIGN homologue of Trp-258, is positioned near the interface between ␣-helix 1 (in portion 1, red, of our CRD swaps) and ␣-helix 2 (in portion 2, green) on adjacent subunits, suggesting a possible role for either or both these residues in dimer formation and/or stabilization.…”
Section: Hiv-1 Transmission (46) Recent Studies Have Also Shown Thatmentioning
confidence: 99%